Preventive Home Visit (PHV) Screening of Hearing and Vision Among Older Adults in Tórshavn, Faroe Islands: A Feasibility Study in a Small-Scale Community - Haanes,Gro Gade; Roin,Ãsa; Petersen,Maria Skaalum (Journal of Multidisciplinary Healthcare, 2021)
Gro Gade Haanes,1 Ãsa Roin,2 Maria Skaalum Petersen2,3 1Faculty of Health and Social Science, Institute for Nursing and Health Science, University of Southeast-Norway (USN), Borre, NO-3199, Norway; 2Centre of Health Sciences, Faculty of Health Sciences, University of the Faroe Islands, Tórshavn, FO-100, Faroe Islands; 3Department of Occupational Medicine and Public Health, The Faroese Hospital System, Tórshavn, FO-100, Faroe IslandsCorrespondence: Gro Gade HaanesFaculty of Health and Social Science, Institute for Nursing and Health Science, University of Southeast-Norway (USN), P.b. 4, 3184, Borre, NO-3199, NorwayTel +47 93437662/ +47 35026499Email groh@usn.noPurpose: Hearing and vision loss are common in later life but often overlooked and undertreated. The study aims to examine hearing and vision as part of preventive home visits (PHV) among 76-year-old home-dwelling citizens in Tórshavn, the capital of Faroe Islands.Patients and Methods: In this cross-sectional study, three specially trained nurses conducted the examinations and tests, for this purpose, in the community health-centre.Results: A total of 74 individuals participated (56% participation rate) of whom 77% had some degree of hearing impairment, 89% had visual impairment and 22% had dual sensory loss. A significant correlation between self-reported hearing ability and clinical findings was found, whereas self-reported vision did not correlate significantly with test-results.Conclusion: Results indicate that implementing clinical assessments of hearing and vision as part of preventive home visits would benefit people receiving visits, and society by helping maintain the conditions that allow them to stay in their own homes for as long as possible.Keywords: hearing, vision, Faroe Islands, preventive home visits